Scott, Dickens, Eliot, Hardy - Poole, Adrian (Great Shakespeareans, 2011)
Great Shakespeareans offers a systematic account of those figures who have had the greatest influence on the interpretation, understanding and cultural reception of Shakespeare, both nationally and internationally. . In this volume, leading scholars assess the contribution of Sir Walter Scott, Charles Dickens, George Eliot and Thomas Hardy to the afterlife and reception of Shakespeare and his plays. Each substantial contribution assesses the double impact of Shakespeare on the figure covered and of the figure on the understanding, interpretation and appreciation of Shakespeare, provide a sket.